Brain Metastasis Mimicking Brain Abscess in ALK-Positive Non-Small-Cell Lung Cancer - Toshio Sakatani; Hidenori Kage; Shunsaku Takayanagi; Kaoru Watanabe; Yoshihisa Hiraishi; Aya Shinozaki-Ushiku; Shota Tanaka; Tetsuo Ushiku; Nobuhito Saito; Takahide Nagase (Case Reports in Oncological Medicine)
Brain metastasis frequently develops in non-small-cell lung cancer (NSCLC). Here, we report a patient who developed brain metastasis from ALK-positive NSCLC which mimicked brain abscess. He was admitted for suspected obstructive pneumonia nine months after curative lung resection. Head magnetic resonance imaging revealed a cavitary lesion, which was compatible with brain abscess but rare in brain metastasis. However, after treatment with antibiotics, the brain lesion increased in size. Aspiration of the liquid content of the brain lesion revealed cancer cells. When a brain lesion suggestive of abscess develops in a patient with ALK-positive NSCLC, aspiration may be necessary to differentiate metastasis from abscess.